Data acquisition and seabed structure mapping using side scan sonar starfish 990F system - Nor Farhana Harun, 1993-; Mohd. Razali Mahmud, supervisor; Fakulti Geoinformasi dan Harta Tanah (2016)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2016